An unusual ocelot–opossum co-occurrence in the Chiquitano dry forest, Bolivia - Nogales-Ascarrunz, Paola; Jordan, Celine; Beukes, Maya; Aramayo Ledezma, Gabriel; Aramayo-Bejarano, Jose Luis; Jansen, Martin (Therya Notes, 2026)
Interspecific interactions among carnivores and their prey are rarely documented beyond classical predation or competition events. Recently, camera traps revealed an unusual spatial and temporal co-occurrence between ocelot (Leopardus pardalis) and common opossum (Didelphis marsupialis) in the Amazonian forest of Perú. Here, we report the first record of this co-occurrence in the Chiquitano dry forest of Bolivia, extending the known ecological context of this observation beyond the Amazonian ecosystem. The record was obtained as part of a long-term camera trap monitoring project carried out since 2017 in the Chiquitano dry forest. The project has 25 stations and spans across 23,025 ha, operating continuously, independent detections were defined using 60-minute intervals. On June 23rd, 2024, one camera trap station recorded the only co-occurrence between an ocelot and a common opossum detected among around 700 independent records of both species. This rare record highlights an unusual spatial and temporal co-occurrence between an ocelot and a common opossum and highlights the importance of long-term camera trap monitoring for documenting uncommon natural history events. Further studies are needed to determine how often and under what conditions such interactions occur and in which ecosystems. This record documents for the first time a spatial and temporal co-ocurrence between and ocelot and a common opossum in the Chiquitano dry forest of Bolivia, extending the geographic range of previous reports from the Peruvian Amazon.